The Routledge handbook of Language and Digital Communication - Georgakopoulou, Alexandra and Spilioti, Tereza (London: Routledge, 2016)
This Handbook provides a comprehensive, state-of-the-art overview of language-focused research on digital communication.
Includes Bibliographic references and index.
Keywords: Digital Literacies--Digital Communication--Language Resources